Olfactory fMRI in Patients with Parkinson's Disease - Hummel, Thomas; Fliessbach, Klaus; Abele, Michael; Okulla, Thorsten; Reden, Jens; Reichmann, Heinz; Wüllner, Ullrich; Haehner, Antje (Frontiers in Integrative Neuroscience, 2010)
Hyposmia is one of the early signs in Idiopathic Parkinson´s Disease (PD). Olfactory stimuli were applied during fMRI scanning to show disease-related modulation of central nervous system structures and to advance our understanding of olfactory dysfunction in PD patients. All participants received either unpleasant stimuli smelling like rotten eggs or pleasant ones smelling like roses. Using a block design at a 1.5 T scanner we investigated a total of 8 PD patients (mean age 60 ± 10.9 years) and 13 age matched controls (mean age 58 ± 9.6 years). PD duration ranged from 1 to 9 years (mean 6.63 years); patients had an average “Unified Parkinson’s Disease Rating Scale III” score of 23.25 (range, 6-46). Olfactory function was established using the “Sniffin’ Sticks” test battery. Patients tended to rate the stimuli presented during fMRI scans as less intense, but also as more pleasant than controls. FMRI results revealed differences between PD patients and controls which depended on the type of stimulation. While both pleasant and unpleasant stimulation was associated with lower activation in the amygdalo-hippocampal complex in patients compared to controls, increased activity in response to pleasant stimuli was observed in the striatum and the left inferior frontal gyrus. In contrast, unpleasant stimulation led to hypoactivation of the ventral striatum in patients (but not in controls) and did not enhance left inferior frontal activity. These results may partly reflect differences between PD patients and healthy controls in the processing of primary dimensions of odors, intensity and valence.